2009
DOI: 10.3748/wjg.15.2638
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant percutaneous radiofrequency ablation of feeding artery of hepatocellular carcinoma before treatment

Abstract: AIM:To evaluate the feasibility and efficacy of percutaneous radiofrequency ablation (RFA) of the feeding artery of hepatocellular carcinoma (HCC) in reducing the blood-flow-induced heat-sink effect of RFA. METHODS:A total of 154 HCC patients with 177 pathologically confirmed hypervascular lesions participated in the study and were randomly assigned into two groups. Seventy-one patients with 75 HCCs (average tumor size, 4.3 ± 1.1 cm) were included in group A, in which the feeding artery of HCC was identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Biliverdin-IX-alpha was shown to inhibit the replication of HCV, HHV-6, and HIV (Mori et al, 1991; Nakagami et al, 1992; Lehmann et al, 2010; Zhu et al, 2010), CO reduced the growth of E. coli , P. aeruginosa , and S. aureus (Nobre et al, 2007, 2009; Davidge et al, 2009; Desmard et al, 2012) and iron almost completely decreased HCV core mRNA and protein (Hou et al, 2009). The results shown in this paper provided original evidence about the antiviral role of BR, the formation of which requires the concerted action of both HO and BVR, thus expanding the cytoprotective role of this linear tetrapyrrole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biliverdin-IX-alpha was shown to inhibit the replication of HCV, HHV-6, and HIV (Mori et al, 1991; Nakagami et al, 1992; Lehmann et al, 2010; Zhu et al, 2010), CO reduced the growth of E. coli , P. aeruginosa , and S. aureus (Nobre et al, 2007, 2009; Davidge et al, 2009; Desmard et al, 2012) and iron almost completely decreased HCV core mRNA and protein (Hou et al, 2009). The results shown in this paper provided original evidence about the antiviral role of BR, the formation of which requires the concerted action of both HO and BVR, thus expanding the cytoprotective role of this linear tetrapyrrole.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the by-products of the HO system involved in this antiviral activity, BV was shown to interfere with human hepatitis C virus (HCV) and human herpes virus (HHV)-6 replication as well as to reduce the cytopathic effect of human immunodeficiency type 1 virus (HIV) in Huh or MT-4 cells (Mori et al, 1991; Nakagami et al, 1992; Lehmann et al, 2010; Zhu et al, 2010). In addition, CO inhibited the growth of enterovirus, E. coli , P. aeruginosa as well as S. aureus (Nobre et al, 2007; Tung et al, 2011; Desmard et al, 2012) and iron almost completely decreased HCV core mRNA and protein (Hou et al, 2009). Taken together these results underlined a major role for HO in antiviral and antibacterial defense.…”
Section: Introductionmentioning
confidence: 99%
“…Most HCC is a hypervascular tumor with its blood supply majorly from hepatic artery. Many factors including intra-tumoral or peri-tumoral heat-sink effect, insufficient ablative margin or the presence of satellite around the target tumor are associated with incomplete ablation and local tumor progression (LTP) [5] , [6] , [7] , [8] , [9] , [10] , [11] .To overcome these limitations, many novel algorithms have been accepted [5] , [6] , [7] , [8] , [9] , [10] , [11] but only one study reported that feeding artery ablation (FAA) before target tumor ablation in HCC >3 cm could reduce LTP [12] .To our knowledge, the effects of FAA for HCC <3 cm or for HCC at difficult-to-ablate location remain unknown. Therefore, the aim of our study is to compare the outcomes between patient with and without FAA before target tumor ablation.…”
mentioning
confidence: 99%
“…At present, there are physical and chemical methods for blocking the nourishing vessels of tumors. Intravascular interventional embolization is the commonly used physical method for treatment of malignant liver tumors [26]. Intravenous infusion of vasoconstrictor drugs is used as a chemical method, and the commonly used drugs are pituitary vasopressin, adrenaline and oxytocin [24].…”
Section: Dose Of Oxytocinmentioning
confidence: 99%